2013
DOI: 10.1016/j.ejmg.2013.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of KCNJ8 in a patient with Cantú syndrome with unique vascular abnormalities – Support for the role of K(ATP) channels in this condition

Abstract: KCNJ8 (NM_004982) encodes the pore forming subunit of one of the ATP-sensitive inwardly rectifying potassium (KATP) channels. KCNJ8 sequence variations are traditionally associated with J-wave syndromes, involving ventricular fibrillation and sudden cardiac death. Recently, the KATP gene ABCC9 (SUR2, NM_020297) has been associated with the multi-organ disorder Cantú syndrome or hypertrichotic osteochondrodysplasia (MIM 239850) (hypertrichosis, macrosomia, osteochondrodysplasia, and cardiomegaly). Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 18 publications
2
95
0
Order By: Relevance
“…Slowed AV nodal conduction and fascicular block are consistent with our findings in mice, but it is important to note that the ECG findings in the patients are made in only a small number of patients, each of whom carried ABCC9 (SUR2) mutations (not KCNJ8 , Kir6.1) and although essentially all reported features of the disease seem to be common to patients with either gene mutated 13,14 we have not carried out similar studies on KCNJ8 patients. It should be noted that several studies have also reported a specific Kir6.1 variant (S422L) to be associated with ‘Jwave’ or ‘early repolarization’ syndrome (ERS), characterized by abnormalities in the J-point of the electrocardiogram 31,32 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Slowed AV nodal conduction and fascicular block are consistent with our findings in mice, but it is important to note that the ECG findings in the patients are made in only a small number of patients, each of whom carried ABCC9 (SUR2) mutations (not KCNJ8 , Kir6.1) and although essentially all reported features of the disease seem to be common to patients with either gene mutated 13,14 we have not carried out similar studies on KCNJ8 patients. It should be noted that several studies have also reported a specific Kir6.1 variant (S422L) to be associated with ‘Jwave’ or ‘early repolarization’ syndrome (ERS), characterized by abnormalities in the J-point of the electrocardiogram 31,32 .…”
Section: Discussionsupporting
confidence: 81%
“…ABCC9 , which encodes the predominant sulfonylurea receptor (SUR2) isoform in the cardiovascular system, have been identified in 18 of 25 individuals with CS 11,12 . Two studies 13,14 have also identified KCNJ8 mutations in CS patients. The demonstration that CS can result from mutations in Kir6.1 14 or SUR2 confirms that CS results from GOF in K ATP channels formed from these subunits.…”
Section: Introductionmentioning
confidence: 99%
“…CS can arise from GOF in either Kir6.1 or SUR2 proteins of the cardiovascular K ATP channel (2)(3)(4)(5). A distinct CS cardiac pathology is characterized by high output state with enhanced cardiac contractility and enhanced chamber volume, associated with decreased vascular pulse wave velocity and low BP.…”
Section: Feedback Control Via L-type Ca Current In Compensated Cardiacmentioning
confidence: 99%
“…KATP | transgenic | cardiovascular system | KCNJ8 | Kir6.1 C antu syndrome (CS), characterized by hypertrichosis, osteochondrodysplasia, and multiple cardiovascular abnormalities (1), is caused by gain-of-function (GOF) mutations in the genes encoding the pore-forming (Kir6.1, KCNJ8) and regulatory (SUR2, ABCC9) subunits of the predominantly cardiovascular isoforms of the K ATP channel (2)(3)(4)(5). Because the same disease features arise from mutations in either of these subunits, it is concluded that CS arises from increased K ATP channel activity, as opposed to any nonelectrophysiologic function of either subunit.…”
mentioning
confidence: 99%
“…The ABCC9 gene encodes the channel regulation protein SUR2, which acts as part of an adenosine triphosphate-sensitive potassium channel. Mutations in the KCNJ8 gene, which encodes another component of an adenosine triphosphatesensitive potassium channel, have also been shown to cause the Cantú syndrome phenotype [4]. The exact mechanisms by which abnormalities of the channel protein lead to the observed phenotype remain unclear.…”
Section: Discussionmentioning
confidence: 99%